PIBID as the “third space” in the initial formation of teachers - dos Santos Felício, Helena Maria (Revista Diálogo Educacional, 2014)
This work aims to analyze the perceptions of the undergraduates involved with the Institutional Scholarship Program for New Teachers (PIBID) of the Federal University of Alfenas (UNIFAL-MG) concerning the development of this program as a space-time to the professional formation of teachers. Zeichner (2010) studies the concept of “third space”, eliminating the polarities between theory and practice towards the creation of space(s)- time(s) that gather practical and academic knowledge or skills in less hierarchical settings, having as objective the creation of new learning opportunities for future teachers. From this concept, we qualitatively analyzed the experiences of the students that took part in the PIBID from 2010 to 2012, from the assumptions of methodological studies of narratives, establishing as categories the information concerning the theory-practice relationship, the relationship between School and University, the school reality and the reality of education, and the initial and continuing training of teachers. According to the results, the PIBID, as a public policy to initiate the professional formation of teachers, should influence the teaching career policies and the policies that define the work conditions of teachers, since the PIBID is, to the undergraduate students, a fundamental space-time to consolidate a high-quality education for teachers; however, they intend to teach in higher education.